The struggle of African Indigenous knowledge systems in an age of globalization : a case for children's traditional games in South-Eastern Zimbabwe - Mawere, Munyaradzi (Langaa Research & Publishing, 2012)
This is a comprehensive study and erudite description of the struggle of African Indigenous knowledge systems in an age of globalization, using in particular eighty-four traditional children's games in south-eastern Zimbabwe. The book is an informative and interesting anthropological account of rare African children's games at the risk of disappearing under globalization. The virtue of the book does not only lie in its modest philosophical questioning of those knowledge forms that consider themselves as superior to others, but in its healthy appreciation of the creative art forms of traditional literature that features in genres such as endangered children's traditional games. The book is a clarion call to Africans and the world beyond to come to the rescue of relegated and marginalized African creativity in the interest of future generations.